2012
DOI: 10.1093/rheumatology/kes358
|View full text |Cite
|
Sign up to set email alerts
|

Necessity of early intervention for IgG4-related disease--delayed treatment induces fibrosis progression

Abstract: Salivary secretion can be improved even in cases with lower levels of salivary secretion before treatment in IgG4-RD, but improvements in the amount of salivary secretion decrease with histological changes with delayed therapeutic intervention. These data suggest that early intervention is needed to improve outcomes in patients with IgG4-MD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(53 citation statements)
references
References 13 publications
1
50
0
2
Order By: Relevance
“…Previous reports have also described that the clinical presentation and pathology may be distinct according to the damaged tissues (3,22,23). As evidenced in other inflammatory disorders, inflammatory cell infiltration may be observed in the early stage of IgG4-RD and inflammation is replaced with severe fibrosis in the advance stage (2,24).…”
Section: Discussionmentioning
confidence: 86%
“…Previous reports have also described that the clinical presentation and pathology may be distinct according to the damaged tissues (3,22,23). As evidenced in other inflammatory disorders, inflammatory cell infiltration may be observed in the early stage of IgG4-RD and inflammation is replaced with severe fibrosis in the advance stage (2,24).…”
Section: Discussionmentioning
confidence: 86%
“…15 Biopsies of the inflamed tissues are the only warrant of a prompt and accurate diagnosis in this condition. FDG-PET scan is the most useful radiological examination to investigate for other organs involvement and to find the most accessible sites to proceed to a biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…As our study indicates, type 1 AIP is often accompanied by other immunologic diseases, the most common being sialadenitis (75%). Shimizu et al [14] found that salivary secretion could be improved even in cases with lower levels of salivation before treatment. When the B lymphocytes of the pancreas are inhibited by T lymphocytes and cytokine secreted by macrophages, they will accompany DM with a rate of 33%.…”
Section: Discussionmentioning
confidence: 99%